"Measuring the Mix" of Policy Responses to COVID-19: Comparative Policy Analysis Using Topic Modelling. Issue 2 (4th March 2021) - Goyal, Nihit; Howlett, Michael
Abstract: Although understanding initial responses to a crisis such as COVID-19 is important, existing research on the topic has not been systematically comparative. This study uses topic modeling to inductively analyze over 13, 000 COVID-19 policies worldwide. This technique enables the COVID-19 policy mixes to be characterized and their cross-country variation to be compared. Significant variation was found in the intensity, density, and balance of policy mixes adopted across countries, over time, and by level of government. This study advances research on policy responses to the pandemic, specifically, and the operationalization of policy mixes, more generally.